Water implications of foreign direct investment in Ethiopia's agricultural sector - Bossio, Deborah A.; Erkossa, Teklu; Dile, Y.T.; McCartney, Matthew P.; Killiches, F.; Hoff, H. (2012)
Ethiopia is often highlighted as a country in which a lot of foreign land acquisition is occurring. The extent to which these investments also constitute significant acquisitions of water is the subject of this paper. It is apparent that water availability is a strong driver of the recent surge of investments in agricultural land globally, and in general the investments occur in countries with significant 'untapped' water resources. Ethiopia is no exception. We propose that the perception of unused and abundant water resources, as captured in dominant narratives, that drives and justifies both foreign and domestic investments, fails to reflect the more complex reality on the ground. Based on new collections of lease information and crop modelling, we estimate the potential additional water use associated with foreign investments at various scales. As a consequence of data limitations our analyses provide only crude estimates of consumptive water use and indicate a wide range of possible water consumption depending on exactly how foreign direct investment (FDI) development scenarios unfold. However, they do suggest that if all planned FDI schemes are implemented and expanded in the near future, additional water consumption is likely to be comparable with existing water use in non-FDI irrigation schemes, and a non-trivial proportion of the countrys water resources will be effectively utilised by foreign entities. Hence, additional water use as well as local water scarcity ought to be strong considerations in regulating or pricing land leases. If new investments are to increase local food and water security without compromising local and downstream water availability they should be designed to improve often very low agricultural water productivity, and to safeguard access of local populations to water.